Reflux Laryngitis: Correlation between the Symptoms Findings and Indirect Laryngoscopy - Silva, Carlos Eduardo Dilen da; Niedermeier, Bruno Taccola; Portinho, Fernando (International Archives of Otorhinolaryngology, 2015)
Introduction The indirect laryngoscopy has an important role in the characterization of reflux laryngitis. Although many findings are nonspecific, some strongly suggest that the inflammation is the cause of reflux.Objective The aim of this study was to evaluate the correlation between reflux symptoms and the findings of indirect laryngoscopy.Methods We evaluated 27 patients with symptoms of pharyngolaryngeal reflux disease.Results Laryngoscopy demonstrated in all patients the presence of hypertrophy of the posterior commissure and laryngeal edema. The most frequent symptoms were the presence of dry cough and foreign body sensation.Conclusion There was a correlation between the findings at laryngoscopy and symptoms of reflux.
Keywords: laryngitis; laryngoscopy; gastroesophageal reflux